Effects of increasing AA ratios, SBM and DDGS on performance and carcass characteristics of finishing pigs and the inclusion of HiPhorius Phytase on nursery and finishing pig growth performance, carcass characteristics, serum chemistry, and bone mineralization - Reeb, Macie Elizabeth (Kansas State University, 2023)
This thesis includes three chapters addressing very practical questions facing swine nutritionists including replacing soybean meal with dried distillers grain with solubles and feed-grade amino acids and the addition of a novel phytase source in nursery and finishing pigs. Two experiments using a total of 1,701 finishing pigs was used to determine the effect of amino acid adjustments, soybean meal and dried distillers grain with solubles inclusion on performance and carcass characteristics of finishing pigs. In Exp.1 no effect was observed on growth performance based on dietary amino acid adjustment. In Exp. 2, an improvement in feed efficiency was observed in pigs fed dried distillers grain with solubles -based diets with an amino acid adjustment. Additionally, two experiments using a total of 2,321 pigs were conducted to evaluate the inclusion of HiPhorius phytase on growth performance, serum chemistry, carcass characteristics, and bone mineralization o finishing pigs. Decreased growth performance (Exp.1) as well as bone mineralization (Exp.2) was observed, indicating that the phytase release provided by the phytase was less than the assumed release used in diet formulation. Finally, another experiment with 297 nursery pigs was conducted to determine the effects of HiPhorius phytase on nursery pig growth performance and bone mineralization. Increasing phytase in diets formulated below the pig’s P requirement improved growth performance and bone mineralization. Increasing phytase in diets with 0.27% aP did not influence growth performance, but improved bone mineralization. In summary, these experiments provide data on the efficacy of a new phytase source in nursery and finishing pigs, and additional insight on the interrelationship of branch-chain amino acids and large neutral amino acids in diets containing dried distillers grain with solubles in finishing pigs.
Keywords: Bone ash; Bone density; Phytase; Branched-chain amino acids; Dried distillers grains; Soybean meal